Microfluidics-based assay on the effects of microenvironmental geometry and aqueous flow on bacterial adhesion behaviors - Yang Liu; Jian-Chun Wang; Li Ren; Qin Tu; Wen-Ming Liu; Xue-Qin Wang; Rui Liu; Yan-Rong Zhang; Jin-Yi Wang (Elsevier, 2011)
A new microfluidic system with four different microchambers (a circle and three equilateral concave polygons) was designed and fabricated using poly(dimethylsiloxane) (PDMS) and the soft lithography method. Using this microfluidic device at six flow rates (5, 10, 20, 30, 40, and 50Â Î¼L/h), the effects of microenvironmental geometry and aqueous flow on bacterial adhesion behaviors were investigated. Escherichia coli HB101 pGLO, which could produce a green fluorescent protein induced by l-arabinose, was utilized as the model bacteria. The results demonstrated that bacterial adhesion was significantly related to culture time, microenvironment geometry, and aqueous flow rates. Adhered bacterial density increased with the culture time. Initially, the adhesion occurred at the microchamber sides, and then the entire chamber was gradually covered with increased culture time. Adhesion densities in the side zones were larger than those in the center zones because of the lower shearing force in the side zone. Also, the adhesion densities in the complex chambers were larger than those in the simple chambers. At low flow rates, the orientation of adhered bacteria was random and disorderly. At high flow rates, bacterial orientation became close to the streamline and oriented toward the flow direction. All these results implied that bacterial adhesion tended to occur in complicated aqueous flow areas. The present study provided an on-chip flow system for physiological behavior of biological cells, as well as provided a strategic cue for the prevention of bacterial infection and biofilm formation. Keywords: Microfluidic device, Escherichia coli, Adhesion behaviors, Geometry, Aqueous flow